Targeted degradation of α-Synuclein using an evolved botulinum toxin protease - Philipp Sondermann; Christian S. Diercks; Cynthia Rong; Peter G. Schultz (Proceedings of the National Academy of Sciences, 2025)
There is considerable interest in the targeted degradation of proteins implicated in human disease. The use of sequence-specific proteases for this purpose is severely limited by the difficulty in engineering the numerous enzyme–substrate interactions required to yield highly selective proteases while maintaining catalytic activity. Herein, we report a strategy to evolve a protease for the programmed degradation of α-Synuclein, a presynaptic protein closely linked to Parkinson’s disease. Our structure-guided evolution campaign uses the protease from botulinum neurotoxin and showcases the stepwise change of specificity from its native substrate SNAP25 to the selective degradation of α-Synuclein. The protease’s selectivity is further demonstrated in human cells where near complete degradation of overexpressed human α-Synuclein is observed with no significant effects on cell proliferation. This stepwise strategy may serve as a general approach to evolve highly selective proteases targeting dysregulated proteins.